Improving the Model of HRM Practices and the Trade Unions in Simultaneous with Key Role of Iraq law - Shirzad Mohammed Mahdi; Bnar Abdulmajeed Ghafour; Ali Abdullah Ahmed; Mansoor Nooruldeen Hasan (Eurasian Journal of Management & Social Sciences)
This research paper demonstrates the concerns and practices of HRM at the enterprise level in response to the recent World Trade Organization accession, also investigate issues including the question of convergence of global markets, the issue of Social protection improvement and its consequences, and the Economic policy implications. To answer the research questions, a survey was conducted, from the sample of 340 employees, 228 questionnaires were completed, constituting a response rate of (64.9%). Deletion of missing values resulted in a usable sample of 174 Businessmen and employees.  The results showed that there was a positive correlation between HRM practice and trade unions. The implications of this study could be valuable for various ownership, location, size, sector, markets, and promote the way of dealing with a variety of challenges and HRM practices that may be related to Iraq law, trade unions organization accession, and Economics.